2017
DOI: 10.1007/978-3-319-63245-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcription Factors in Pulmonary Artery Smooth Muscle Cells: An Important Link to Hypoxic Pulmonary Hypertension

Abstract: Hypoxia, namely a lack of oxygen in the blood, induces pulmonary vasoconstriction and vasoremodeling, which serve as essential pathologic factors leading to pulmonary hypertension (PH). The underlying molecular mechanisms are uncertain; however, pulmonary artery smooth muscle cells (PASMCs) play an essential role in hypoxia-induced pulmonary vasoconstriction, vasoremodeling, and PH. Hypoxia causes oxidative damage to DNAs, proteins, and lipids. This damage (oxidative stress) modulates the activity of ion chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 206 publications
0
6
0
Order By: Relevance
“…Studies have shown that oxidative stress or exacerbated levels of ROS (specifically superoxide and hydrogen peroxide) are necessary to increase [Ca 2+ ] i under hypoxic conditions; this concentration increase is realized through voltage-dependent calcium channels (VDCCs) in PASMCs [ 89 , 90 , 91 ] and causes PASMC contraction and increases in pulmonary artery pressure.…”
Section: Oxidative Stress and High-altitude Diseasesmentioning
confidence: 99%
“…Studies have shown that oxidative stress or exacerbated levels of ROS (specifically superoxide and hydrogen peroxide) are necessary to increase [Ca 2+ ] i under hypoxic conditions; this concentration increase is realized through voltage-dependent calcium channels (VDCCs) in PASMCs [ 89 , 90 , 91 ] and causes PASMC contraction and increases in pulmonary artery pressure.…”
Section: Oxidative Stress and High-altitude Diseasesmentioning
confidence: 99%
“…Precise transcriptional regulation of protein-encoding genes is critical for cell proliferation, differentiation, and development ( Thomas and Chiang, 2006 ). TFs are considered to play vital roles in the development of pulmonary hypertension through pro-inflammatory, immunological, and multiple other cellular responses ( Di Mise et al, 2017 ). To our knowledge, this is the first study to show that TFs RBBP9, GATA3, and TAF1 may be involved in the development of IPAH.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of c-jun and c-fos can be upregulated by calcium influx and is much higher in lung vessels from IPAH patients and modeled PAH rats than normal. Therefore, the Ca 2+ /c-jun and c-fos pathway may also be a signaling pathway for PASMCs proliferation [29,39]. Although there is no evidence that TRPV1 is responsible for this pathway, we cannot exclude the existence of the TRPV1/Ca 2+ /c-jun(c-fos) pathway in PAH; further investigation is needed.…”
Section: C-jun and C-fosmentioning
confidence: 98%
“…CREB is a Ca 2+ -dependent TF that modulates gene expression by binding to the promoter region of target genes after translocating into the nucleus. This translocation necessitates its phosphorylation by Ca 2+ /CaM-dependent protein kinase II and Ca 2 + /CaM-dependent protein kinase IV [27,29]. The pCREB has been found to be significantly upregulated in IPAH PASMCs, accompanied by increased TRPV1 and [Ca 2+ ] i .…”
Section: Crebmentioning
confidence: 99%
See 1 more Smart Citation